2022
DOI: 10.20944/preprints202207.0351.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health-Related Quality of Life of Tuberculosis Patients During the COVID-19 Pandemic in Conakry, Guinea: A Mixed Methods Study

Abstract: The COVID-19 pandemic has had a significant impact on all facets of life and has exacerbated many challenges faced by people living with tuberculosis (TB). This study aimed to assess the health-related quality of life (HRQoL) of TB patients in Guinea during the COVID-19 pandemic. A mixed-methods study was conducted using two validated psychometric tools to assess HRQoL and qualitative interviews among TB patients enrolled in treatment at three centers in Conakry, Guinea. Multinomial logistic regression was use… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Despite the abundance of quantitative evidence of the pandemic's impact on TB diagnoses, there have been few published reports describing the ways in which the pandemic affected people's pathway to diagnosis from their own perspectives. Qualitative studies exploring patients' experience with TB during the pandemic have reported patients' concerns around the financial and social costs of lockdowns, their ability to continue accessing TB medications, and their fear of infection [8][9][10][11]. However, these studies have not identified ways in which the pandemic had impacted patients' experience obtaining a TB diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the abundance of quantitative evidence of the pandemic's impact on TB diagnoses, there have been few published reports describing the ways in which the pandemic affected people's pathway to diagnosis from their own perspectives. Qualitative studies exploring patients' experience with TB during the pandemic have reported patients' concerns around the financial and social costs of lockdowns, their ability to continue accessing TB medications, and their fear of infection [8][9][10][11]. However, these studies have not identified ways in which the pandemic had impacted patients' experience obtaining a TB diagnosis.…”
Section: Introductionmentioning
confidence: 99%